PROMOTING POLYSULFIDES REDOX CONVERSION BY SULFUR-DEFICIENT ZNS1 X HOLLOW POLYHEDRONS FOR LITHIUM-SULFUR BATTERIES - Gao, Wanjie; Jin, Qianwen; Liu, Yanyu; Zhang, Yongguang; Wang, Xin; Bakenov, Zhumabay (Materials & Design, 2021)
Lithium-sulfur (Li-S) batteries are deemed as the attractive systems for high-energy storage. However, the polysulfides shuttling with slow redox kinetics has seriously hindered their practical applications. Herein, sulfur-deficient zinc sulfide (ZnS1 x) hollow polyhedrons are synthesized as the multifunctional sulfur host material via the sulfurization and high-temperature annealing method. The unique hollow structure could supply adequate void spaces for sulfur loading and alleviate volumetric expansion of sul fur upon the cycling process. Besides, ZnS1 x hollow polyhedrons with abundant sulfur vacancies can pro vide effective adsorption sites to chemically immobilize polysulfides and enhance polysulfides redox conversion as confirmed by theoretical calculation results and electrocatalytical experiments. Thus, the S/ZnS1 x cathode delivers the remarkable initial capacity (1206 mAh g 1 at 0.2 C) and excellent cycling stability (592 mAh g 1 after 500 cycles at 1 C). The study points out the idea of functional cathode mate rial for Li-S batteries based on a simple yet efficient vacancy engineering metho
Keywords: Type of access: Open Access; Sulfur-deficient; Hollow structure; Sulfur host; Polysulfides redox conversion; Lithium-sulfur battery